APPLICATION OF A LEARNING MANAGEMENT SYSTEM ON A DIGITAL PLATFORM FOR THE PROFESSIONAL TRAINING OF SKILLED WORKERS IN THE ENGINEERING INDUSTRY (Innovative professional education, 2025)
The article examines the methods of integrating and applying a Learning Management System (LMS) on digital platforms for the professional training of qualified workers in the machine-building industry. In the context of education digitalization, innovative technologies enhance the learning process’s efficiency by providing access to interactive tools, flexible educational materials, and personalized assessment approaches.
Keywords: digitalization, Microsoft Teams, LMS, professional training, machine-building, integration, teachers, testing, assessment, interaction